PENERAPAN PRINSIP-PRINSIP MANAJEMEN DALAM KEPEMIMPINAN DI SEKOLAH TINGGI ILMU SOSIAL DAN ILMU POLITIK MUHAMMADIYAH RAPPANG KABUPATEN SIDENRENG RAPPANG PROVINSI SULAWESI SELATAN - Kamaruddin Sellang; Muh. Darman (AkMen JURNAL ILMIAH, 2017)
The main study in this research is the application of management principles in leadership at the College of Social and Political Science Muhammadiyah Rappang. The population is taken from the element of permanent lecturer and educational staff with a population of 38 people, determined a sample of 38 people with saturated sample technique. Type of research is descriptive quantitative. Data were collected through observation techniques, literature, and questionnaires. Data processing is measured using five Likert scale according to Sugiyono which has been modified by the author. The result of the research shows that the Leadership of Muhammadiyah Rappang School of Social and Political Science has applied to fourteen management principles according to Henry Fayol. The average of each indicator is included in the "Applied" criteria. Three indicators are; unity of direction, fair compensation, and the spirit of unity is included in the criterion "highly applied", while eleven other indicators are included in the "applied" criterion. Leadership at the Collaborative College of Social and Political Science Muhammadiyah Rappang has greatly built the spirit of unity of direction, paying close attention to the easy, effective and efficient salary payment system, on time, and compensating fairly. This is according to the attitude of respondents who rate 85% "applied".